Drivers of Biodiversity Conservation in Sacred Groves: A Comparative Study of Three Sacred Groves in Southwest Nigeria - Adeyanju, S.; Bulkan, J.; Onyekwelu, J.; Peterson St-Laurent, G.; Kozak, R.; Sunderland, T.C.H.; Stimm, B. (MDPI, 2021)
Globally, sacred groves represent a traditional form of community-based conservation system, recognized for their capacity to preserve areas that are of cultural and religious importance to local people. In most cases, the entire community takes on a watchdog role to guard against encroachment and unauthorized access either by its members or outsiders who might desecrate such sites. Our paper investigates the effects of different governance arrangements on three sacred groves in southwest Nigeria⎯Osun Osogbo Sacred Grove (UNESCO World Heritage Site); Idanre Hills (Nigerian National Monument) and Igbo-Olodumare (local cultural site)⎯on their socio-economic and religio-cultural benefits and contribution to biodiversity conservation. Using a mixed-methods design of a semi-structured questionnaire (n=167), key informant interviews (n=2), and focus groups (n=7), we collected data from local community members, traditional priests, sacred grove devotees and tourism officials. We found that customary institutions have guided reverence for sacralized spaces and wise utilization of their unique resources. The growing recognition of sacred groves has paved the way for socioeconomic rewards for individuals and government as cultural tourism increases. We found that the involvement of formal institutions alongside customary institutions in sacred grove management reinforces compliance with conservation laws within the sacred groves, especially where traditional norms are weak or may be disregarded. We discuss the implications of these observations and offer suggestions to improve community engagement, uphold traditional ecological knowledge, and develop ecotourism within the groves. We conclude that the co-existence of community-based conservation through a system of established traditional norms and prohibitions as well as formal government legislation and management, offers assurance for the long-term preservation of sacred groves and their biodiversity.